DAMPAK PENGEMBANGAN JALAN USAHA TANI (JUT) PADA PENINGKATAN PENDAPATAN USAHATANI DI KABUPATEN LEBAK - Erry Yanuar; Asep Mulya Hidayat; Agus M Tauchid S; Tubagus Bahtiar Rusbana; Asih Mulyaningsih; Siti Widiati (JURNAL AGRIBISNIS TERPADU, 2022)
Farm Business Road (JUT) is a road that is usually known as an agricultural road, this road is one of the tools and types of infrastructure needed in the agricultural sector, especially in supporting agribusiness activities. The application of JUT is one of the strategies in developing agricultural areas, JUT can facilitate the distribution of agricultural products, especially in lowland rice commodities. JUT is a form of supporting adequate agricultural infrastructure in farming activities, such as road access for the transportation of agricultural products, this is very much needed to support effective and efficient agricultural development. The application of JUT to lowland rice farming in Wanasalam District can have a positive impact on farming including: 1) Reducing transportation costs/increasing farmers' profits. 2) Facilitate transportation during the rainy season where usually the grain is not transported because of the rainy season so the grain turns black and the grain grows into seeds. 3) With the JUT, quality, quantity and continuity can be achieved because the means of transportation are smooth. The application of JUT shows a difference in production efficiency because JUT is 14.3% more efficient than before the existence of JUT. The greater the efficiency ratio, the more efficient rice production in Wanasalam. Production is more efficient when production input has been minimized in the same amount of production